2022
DOI: 10.3171/2020.11.jns203684
|View full text |Cite
|
Sign up to set email alerts
|

Failure modes and effects analysis of mechanical thrombectomy for stroke discovered in human brains

Abstract: OBJECTIVE Despite advancement of thrombectomy technologies for large-vessel occlusion (LVO) stroke and increased user experience, complete recanalization rates linger around 50%, and one-third of patients who have undergone successful recanalization still experience poor neurological outcomes. To enhance the understanding of the biomechanics and failure modes, the authors conducted an experimental analysis of the interaction of emboli/artery/devices in the first human brain test platform for LVO stroke describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Such a failure mechanism has been reported in ex vivo human brains. 6 It has also been reported that the incidence rate of symptomatic intracranial hemorrhage was .3 times higher for M2 occlusions than for M1 occlusions. 13 Our findings reveal that thrombectomy in the M2 branches results in more frequent and severe collapse and could, therefore, lead to microvascular avulsions during arterial traction.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Such a failure mechanism has been reported in ex vivo human brains. 6 It has also been reported that the incidence rate of symptomatic intracranial hemorrhage was .3 times higher for M2 occlusions than for M1 occlusions. 13 Our findings reveal that thrombectomy in the M2 branches results in more frequent and severe collapse and could, therefore, lead to microvascular avulsions during arterial traction.…”
Section: Discussionmentioning
confidence: 91%
“…To mechanistically validate the in vivo observations and to better understand the impact of different variables in the likelihood of arterial collapse by an experimental design, we used a validated human brain model. 6,7 Unlike the other models using rigid or semirigid arterial phantoms, [9][10][11] this validated model uses fresh human cerebral vessels (ie, flexible and collapsible arteries) and can reproduce different physiologic hemodynamic conditions. On connection of the catheter to the vacuum, we frequently observed collapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Residual occlusion in small branching and perforating arteries is believed to be one of the reasons for poor neurologic outcome despite apparently "complete" recanalization, and this model may be of benefit to better characterize this problem and develop solutions. 14 Second, the human brain model provides a realistic mechanical response of the arteries to the mechanical load of devices. This is critical to accurately test arterial deformation, stretching, collapse under vacuum, and even arterial injury such as perforation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the realistic mechanical properties of the vessel wall make this model unique to reveal failure modes of device-artery interaction such as vessel traction and vessel collapse as shown previously. 14 Pulling back the catheter with weak clot-catheter integration results in residual occlusions or iatrogenic embolization and is likely the main cause of low first-pass recanalization. We think that future aspiration technologies should aim to ingest clots in situ, proximal-to-distal, and at low vacuum power to prevent vessel collapse.…”
Section: Discussionmentioning
confidence: 99%